The Perception Among Students of Sunan Gunung Jati Karawang Vocational School on Learning of VolleyBall - Khuromadhan, Mochammad Gilang; Ismaya, Bambang; Dimyati, Akhmad; izzuddin, Deden akbar (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
This study aims to determine the perceptions of class XII students towards volleyball learning. To find out students' perceptions, the researchers conducted indicators, such as internal factors including attention, mood, experience and memory, while external factors included the uniqueness and contrast of the stimulus, the size and placement of objects or stimuli, motion or movement. The research method uses a survey method using a questionnaire. This research is quantitative descriptive. The population used was the entire class XII. The sampling technique used was the Cluster Random Sampling Technique, Specification Probability Sampling. The sample in this study is one class of five classes. The instrument used in this study used a questionnaire. The score used is the Likert scale. The results of this study indicate that the perceptions of class XII students towards volleyball learning at SMK Sunan Gunung Jati Karawang are in the "very good" category with a percentage of 13.3%, in the "good" category with a percentage of 37.7%, in the "enough" category with a percentage of 35.7%, in the "very sufficient" category with a percentage of 13.3%. The conclusion from the research results of students' perceptions of class XII on volleyball learning at SMK Sunan Gunung Jati Karawang which was obtained using a questionnaire with a percentage of 37.7% being in the "good" category. in the "very sufficient" category with a percentage of 13.3%. The conclusion from the research results of students' perceptions of class XII on volleyball learning at SMK Sunan Gunung Jati Karawang which was obtained using a questionnaire with a percentage of 37.7% being in the "good" category. in the "very sufficient" category with a percentage of 13.3%. The conclusion from the research results of students' perceptions of class XII on volleyball learning at SMK Sunan Gunung Jati Karawang which was obtained using a questionnaire with a percentage of 37.7% being in the "good" category.Key words: Perception, Volleyball, Physical Education Learning